2017
DOI: 10.1016/j.corsci.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

In-coating graphene nano-platelets for environmentally-friendly corrosion protection of iron

Abstract: Highlights GNP-pigmented films show exceptional resistance to cathodic delamination.  Oxygen-diffusion shown to be the rate-limiting step in the presence of GNPs.  Delamination rates correlate with through-coating oxygen permeation rates. A primer coating system adherent to iron substrates based on graphene nano-platelets (GNPs) dispersed in polyvinylbutyral (PVB) is presented. Using a scanning Kelvin probe (SKP), the composite coatings are shown to exhibit exceptional resistance to an important corrosion-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Glover et al also used graphene nanoplatelets that were dispersed in polyvinylbutyral for the protection of iron-based substrates. The durability and associated mechanical stability were found to be appreciable [66]. An advantage associated with the use of polymer-based coatings is that in most cases it is a relatively simple method in terms of functionalization and coating application.…”
Section: Polymer-based Superhydrophobic Coatingsmentioning
confidence: 95%
“…Glover et al also used graphene nanoplatelets that were dispersed in polyvinylbutyral for the protection of iron-based substrates. The durability and associated mechanical stability were found to be appreciable [66]. An advantage associated with the use of polymer-based coatings is that in most cases it is a relatively simple method in terms of functionalization and coating application.…”
Section: Polymer-based Superhydrophobic Coatingsmentioning
confidence: 95%
“…[36][37][38][39][40][41][42][43][44][45][46][47] In recent years, functionalized graphene oxide materials have been reported, such as poly(urea-formaldehyde), tin oxide, plasma based, and epoxy + graphene composite coatings, graphene ink, covalently functionalized N-graphene oxide, and ionic liquids, which are excellent corrosion barrier layers on alloy surfaces because they are impermeable to electrolytes and gas molecues. [48][49][50][51][52][53][54][55][56][57][58] Furthermore, GO functional groups can also enhance electron donation and accepting from the alloy surface. 59,60 The predominant properties of functional graphene oxide materials have a signicant impact on overcoming corrosion failure.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, graphene-based nanocomposite coatings have been found to serve as excellent barriers upon surfaces such as carbon steel 98 and pure iron. 97 It has been hypothesized that the presence of graphene in nano-dimensions, within the organic coating tends to increase the path for the conducting agent to reach the metal/ coating interface. 98 In addition, Glover et al 97 observed a reduction of oxygen diffusion and exceptional resistance to cathodic delamination when graphene nanoplatelets were added into polyvinyl butyral (PVB) coating.…”
Section: Lithium-containing Coatingsmentioning
confidence: 99%
“…97 It has been hypothesized that the presence of graphene in nano-dimensions, within the organic coating tends to increase the path for the conducting agent to reach the metal/ coating interface. 98 In addition, Glover et al 97 observed a reduction of oxygen diffusion and exceptional resistance to cathodic delamination when graphene nanoplatelets were added into polyvinyl butyral (PVB) coating. However, one of the major limitation of this technology is the cost of graphene, which may exceed AUD$130/kg, rendering this technology non-viable for a short term alternative.…”
Section: Lithium-containing Coatingsmentioning
confidence: 99%
See 1 more Smart Citation